1995
DOI: 10.1126/science.7824953
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Regional Cerebral Glucose Metabolism During a Resting State

Abstract: Positron emission tomography was used to evaluate the regional distribution of cerebral glucose metabolism in 61 healthy adults at rest. Although the profile of metabolic activity was similar for men and women, some sex differences and hemispheric asymmetries were detectable. Men had relatively higher metabolism than women in temporal-limbic regions and cerebellum and relatively lower metabolism in cingulate regions. In both sexes, metabolism was relatively higher in left association cortices and the cingulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
164
3
5

Year Published

1995
1995
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 329 publications
(184 citation statements)
references
References 32 publications
10
164
3
5
Order By: Relevance
“…The detection of sex differences was particularly noteworthy, because these differences are rarely appreciated in the R-fMRI literature (35) (37,38). For example, males and females differ in terms of hemoglobin concentrations and hematocrit (39).…”
Section: Resultsmentioning
confidence: 99%
“…The detection of sex differences was particularly noteworthy, because these differences are rarely appreciated in the R-fMRI literature (35) (37,38). For example, males and females differ in terms of hemoglobin concentrations and hematocrit (39).…”
Section: Resultsmentioning
confidence: 99%
“…6 In light of the growing literature demonstrating discrete differences in the brains of men and women, neurobiological substrates may underlie the different clinical trajectories of men and women with addictive disorders. 7,8 In nonaddicted subjects, for example, investigators have reported sex differences in brain structure, 9 basal measures of brain functioning, 10,11 and functional measures of neural responding. 12 Several studies have now documented basal neural differences in cocaine-dependent men and women, including a relative absence of cerebral perfusion defects, 13 less frontal cortex neuronal loss, 14 and better white-matter blood flow 15 in women relative to men.…”
Section: Introductionmentioning
confidence: 99%
“…Many parameters of brain function and structure vary between men and women (eg Gur et al, 1995;Murphy et al, 1996;De Courten-Myers, 1999;De Bellis et al, 2001;Goldstein et al, 2001;Preece and Cairns, 2003;De Vries, 2004), and most psychiatric disorders show sex differences in one or more variables including incidence, age at onset, clinical features, and outcome (eg Lensi et al, 1996;Tamminga, 1997;Piccinelli and Wilkinson, 2000;Aleman et al, 2003;Baron-Cohen et al, 2005). These dimorphisms are usually ascribed primarily to the influence of sex hormones (Collaer and Hines, 1995;Rubinow and Schmidt, 1996;Seeman, 1997;Kelly et al, 1999), as well as to the actions of sex chromosome genes (Vawter et al, 2004;Cutter et al, 2006;Davies and Wilkinson, 2006).…”
mentioning
confidence: 99%